The research of entropy characteristics of circadian dynamics with pulse and motion of rr interval from peoples before and after physical load (Experimental biology, 2018)
First, the features of circadian dynamics of mean value with pulse and motion of RR interval have been formed and analyzed from young people before and after physical load. It is indicated that sizes of heart rates after physical load increased with respect of norm to statistically authentic value (P ≤0,05). Thus, the characteristics of pulse are varied from 69,7 ±3,9 beats per minute up to 77,5±5,5 beats per minute before physical load, and after physical load they are varied from 101,7±6,4 beats per minute up to 110,1±6,0 beats per minute. The value of motion of RR interval before physical load are varied from 0,127±0,09 sec up to 0,147±0,12 sec and after physical load they are varied from 0,087±0,01 sec up to 0,111±0,08 sec. It is discovered that the values of motion of RR interval after physical load are lower than   before physical load. So, the values of pulse entropy before physical load are equal to 0,6165 and after physical load to 0,6668 and the value of motion of RR interval before physical load is equal to 0,5749 and after load equal to 0,5432. The entropy characteristics of circadian   dynamics with pulse after physical load grows and motion of RR interval reduces alternatively.
Keywords: man, circadian rhythms, pulse, motion of RR interval, physical load, entropy.